Detection of the in vitro modulation of Plasmodium falciparum Arf1 by Sec7 and ArfGAP domains using a colorimetric plate-based assay - Swart, Tarryn; Khan, Farrah D.; Ntlantsana, Apelele; Laming, Dustin; Veale, Clinton G. L.; Przyborski, Jude M.; Edkins, Adrienne L.; Hoppe, Heinrich C. (Scientific reports, 2020)
The regulation of human Arf1 GTPase activity by ArfGEFs that stimulate GDP/GTP exchange and ArfGAPs that mediate GTP hydrolysis has attracted attention for the discovery of Arf1 inhibitors as potential anti-cancer agents. The malaria parasite Plasmodium falciparum encodes a Sec7 domain-containing protein - presumably an ArfGEF - and two putative ArfGAPs, as well as an Arf1 homologue (PfArf1) that is essential for blood-stage parasite viability. However, ArfGEF and ArfGAP-mediated activation/deactivation of PfArf1 has not been demonstrated. In this study, we established an in vitro colorimetric microtiter plate-based assay to detect the activation status of truncated human and P. falciparum Arf1 and used it to demonstrate the activation of both proteins by the Sec7 domain of ARNO, their deactivation by the GAP domain of human ArfGAP1 and the inhibition of the respective reactions by the compounds SecinH3 and QS11. In addition, we found that the GAP domains of both P. falciparum ArfGAPs have activities equivalent to that of human ArfGAP1, but are insensitive to QS11. Library screening identified a novel inhibitor which selectively inhibits one of the P. falciparum GAP domains (IC50 4.7 µM), suggesting that the assay format is suitable for screening compound collections for inhibitors of Arf1 regulatory proteins.
Gesehen am 17.09.2020